Factors Affecting Patient Adherence to Pharmacological Therapy in Gout Arthritis and Hyperuricemia - Dzaki Edmonda Setyawan; Endang Mahati; Nani Maharani (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Abstract Background: Pharmacological therapy to reduce serum uric acid levels in gouty arthritis and hyperuricemia patients is essential to prevent gout flare and other hyperuricemia-related morbidities. However, only about 50% of gout arthritis patients adhered to their treatment. Knowing the factors influencing adherence to therapy can be used as a reference for health services to improve adherence.Objective: This study aimed to analyze the factors that influenced the patient's adherence to gouty arthritis and hyperuricemia pharmacological therapy.Methods: This was an observational study with a cross-sectional approach. Subjects were the patients in Wuryantoro Community Health Center, Wonogiri Regency, diagnosed with gouty arthritis or hyperuricemia due to a disorder in purine metabolism. Sampling was done by a consecutive sampling method. Questionnaires with the related medical record were used to collect the necessary data. Research variables were knowledge, attitudes and behavior, gender, age, occupation, insurance, distance from residence to health care facilities, and adherence to therapy which was in binary.Results: Sixty-one percent from a total of 41 respondents were found to be non-adherence to pharmacological therapy. Knowledge, attitudes, and behavior towards therapy, educational level, availability of health insurance, and distance to health facilities were significantly correlated to treatment adherence (p < 0.05). Sex, age, and occupation were not correlated to adherence.Conclusion: Factors influencing adherence were knowledge, attitudes and behavior, academic background, insurance, and the distance from residence to health care facilities.